The Wounds of COVID-19 and Responses to the Challenges: A Commentary on India's Macroeconomic Scenario. Issue 4 (December 2020) - Pant, Vimal; Pathak, Prachi
The COVID pandemic has ravaged the economic health of all countries round the world. This work is a commentary on the scale of the impact the disease has created on the economy and how the country has responded to the challenge. It looks into the interventions of the government as well as their possible implications on the macroeconomic health of the country. We have also suggested measures that could assist in redeeming the economic health and bringing out the vulnerable businesses from existential crisis. JEL Classification Codes: E00, E20, E23, E24, E32